University technology transfer: assessment of invention disclosures by technology transfer offices. (23rd February 2023) - Rocha, António; Cruz-Cunha, Maria Manuela; Romero, Fernando
University technology transfer offices (TTOs) encourage researchers to disclose their inventive results to assess their novelty, industrial applicability, and inventive step to protect and devise a plan to gather the necessary resources for its deployment. To describe the invention disclosure process and to gain knowledge about assessment practices to understand the invention, its market, potential for transfer, and accessibility to finance, Portuguese university TTOs were asked to provide information on their internal processes through a semi- structured survey. The most frequent practices have been identified, including, the analysis of all the technology applications, the assessment of the technology readiness level, patentability, strength of its claims, and protection costs; assessment of the extent of technology demand and potential licensees; and analysis of available sources of finance. The approach was essentially descriptive and exploratory to convey information on how to proceed to guide the initial evaluation that triggers the valorisation process.